Economic assessment of biomass gasification and pyrolysis: A review. Issue 11 (2nd November 2017) - Jin, Cheng-Lin; Wu, Zhen-Mei; Wang, Shu-Wen; Cai, Zheng-Qun; Chen, Ting; Farahani, Mohammad Reza; Li, De-Xun
ABSTRACT: Biomass is a renewable source of energy and an attractive fuel for generating transportations fuels. The amount of solid biomass available in China is huge, such as large amount of agricultural wastes and wood wastes. For the scattered distribution of resources which were waste seriously in China and the relatively low cost, the small and medium-sized gasification plants have a significant competitive advantage to produce energy from biomass that can be classified depending on the fluidizing agents, reaction temperature, system pressure, and hydrodynamic characteristics of the bed. The following review summarizes the different gasification technologies requirement, advantages and disadvantages of the gasification process as an alternative technique for electricity production, feedstocks properties for gasification purposes, and the economics aspects of the process. Research also focuses on the comparison of the gasification system with other energy systems from the economic and technical points of view. This paper provides a better understanding of the advantages and disadvantages of biomass gasifiers to produce low-tar and high-caloric-value syngas for power generation.